1988
DOI: 10.1161/01.str.19.10.1291
|View full text |Cite
|
Sign up to set email alerts
|

Dementia due to vascular disease--a multifactorial disorder.

Abstract: This review was undertaken to evaluate critically the literature pertaining to vascular dementia with the objective of determining a more useful and scientifically supported definition of vascular dementia, its relation to other causes of dementia, and the biologic mechanisms involved in its causation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

1989
1989
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 60 publications
2
65
0
2
Order By: Relevance
“…Although a few studies have shown decreased CBF with normal aging and in patients with chronic, severe hypertension, 32 -34 positron emission tomography studies have not demonstrated a significant increase in oxygen extraction fraction in either the gray or white matter in elderly persons, 35 suggesting that the diminished perfusion is a response to decreased brain metabolism. 36 Perhaps the most convincing CBF study supporting the low periventricular perfusion theory was provided recently by Fazekas et al 10 Using intravenous xenon 133 and an external scintillation detector system, they studied age-matched groups of asymptomatic patients with and without white matter signal abnormalities on MRI and showed slightly lower gray matter blood flow and significantly lower white matter blood flow in the group with MRI lesions.…”
Section: -7mentioning
confidence: 94%
“…Although a few studies have shown decreased CBF with normal aging and in patients with chronic, severe hypertension, 32 -34 positron emission tomography studies have not demonstrated a significant increase in oxygen extraction fraction in either the gray or white matter in elderly persons, 35 suggesting that the diminished perfusion is a response to decreased brain metabolism. 36 Perhaps the most convincing CBF study supporting the low periventricular perfusion theory was provided recently by Fazekas et al 10 Using intravenous xenon 133 and an external scintillation detector system, they studied age-matched groups of asymptomatic patients with and without white matter signal abnormalities on MRI and showed slightly lower gray matter blood flow and significantly lower white matter blood flow in the group with MRI lesions.…”
Section: -7mentioning
confidence: 94%
“…The observed changes in the subcortical low-flow region with aging could reflect impaired perfusion of the periventricular area due to vascular changes. Al though none of the subjects had severe vascular risk factors or peri ventricular hypodensities on their CT, this finding could precede the peri ventricular leukoencephalopathy seen on CT scans in some pa tients with arterial hypertension and in certain cases of vascular dementia (Scheinberg, 1988). Alterna tively, one could infer that the subcortical white matter tissue as well as neurons are involved in the degenerative process of normal aging.…”
Section: Effect Of Age Sex and Atrophy On Rcbfmentioning
confidence: 95%
“…14 To address this important issue in a cross-sectional study, we related brain MRI lesions to a variety of cognitive and neurobehavioral function tests in an independent, normal elderly population. Brain MRI scans were analyzed for degree of brain atrophy, location and number of lacunar lesions, and grade of PVHs.…”
mentioning
confidence: 99%